Estudio Histoquímico de la Microangiopatía Gingival en Relación a Pacientes Diabéticos con Enfermedad Periodontal - Romero, Roberto (2003)
It was observed in histopatologic study and slight gingiva, collagens fibres and hialino fibroblastos distended that surrounds the arteriola. In moderated gingivitis we can see an arteriola with swelled wall and dilated by hialin tissue like microaneurisms. In moderated periodontitis we can see collagens bands slightly hialins and there is a despolimerization of the collagen mucopolisacarids in advanced periodontitis.